Studies on the efficacy of some rhizome powders in protecting stored mung bean phaseolus radiatus against pulse beetle Callosobruchus chinensis (coleoptera: bruchidae) - Asmanizar; Saragih, Maulana Ansari; Simbolon, Fenti Maimunah (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The study was conducted to determine the efficacy of some rhizome powders of Zingiber officinale var amarum and Zingiber officinale var. officinale, Curcuma xanthorrhiza, Alpinia galanga and Kaempferia galanga against Callosobruchus chinensis in protecting mung bean Phaseolus radiatus. The rhizome powders were admixed with the seed at 1% (w/w). The result showed all of rhizomes powder caused adult mortality 80 to 90% at 5 days after treatment, but powder of Alpinia galanga rhizome showed the fastest mortality (43.75% at 1 day after treatment). The rhizome powder of, Alpinia galanga and Kaempferia galanga provided good protection for mung bean Phaseolus radiatus by reducing number of egg laid, F1 adult emergence, seed damaged and seed weight loss.